O funcionamento discursivo da prática social de adoção: a voz de famílias e de profissionais da rede de apoio e de proteção - Soares, Layane Campos (2024)
Adoption can be characterized as a legal mechanism that allows children and adolescents who have been deprived of their families of origin to be included in a new home. This allows us to understand it as a practice that performs a very important social function - guaranteeing the fundamental right to family and community life for children and teenagers in situations of social vulnerability. Unfortunately, in Brazil, it is evident that not all children and adolescents have their rights guaranteed. The National Council of Justice (Brazil, 2020) reported that 2,991 young people who were in institutional care reached the age of majority between October 2019 and May 2020. This fact allows us to state that we are facing a social problem, which is made up of a discursive/semiotic facet (Chouliaraki; Fairclough, 1999; Fairclough, 2003, 2012). In view of this understanding that this social problem is constructed in and by language and that language is an irreducible part of social life, one that maintains a dialectical and internal relationship with society, we understand that social issues are, in part, discourse issues and vice versa (Chouliaraki; Fairclough, 1999; Fairclough, 2003). We therefore conducted a discursive-ethnographic study (Magalhães; Martins; Resende, 2017) to investigate the discursive functioning of the social practice of adoption and its representation by various social actors. The study was conducted in a virtual environment within two philanthropic organizations located in Uberlândia-MG and Fortaleza-CE, which offer support for adoption applicants and adoptive families. To accomplish this, we utilized the theoretical-methodological contributions of the dialectical-relational approach of Critical Discourse Analysis (Chouliaraki; Fairclough, 1999; Fairclough, 2003), as well as well-supported studies on Appraisal Theory (White, 2004; Martin; White, 2005) and adoption (Marmitt, 1993; Weber, 2003; Paiva, 2004; Carvalho, 2012; Bittencourt, 2013; Barros, 2014; Sena, 2018). The corpus comprises: i) narrative interviews with adoptive families; ii) semi-structured interviews with professionals in the support and protection network; iii) data generated through the transcription of support group meetings, held by the institutions co-participating in this study remotely, in live format, due to the context of the Covid-19 pandemic. The analysis was conducted using interdiscursivity and appraisal as categories. The results clearly indicate that currently the social practice of adoption does not guarantee family life to children and adolescents who have been deprived of their biological families. The evaluation of this practice predominantly consists of negative appreciation of composition and these evaluations show several irregularities and flaws in some adoption process, including non-compliance with legal deadlines, disregard for legal norms, a biological perspective on parenthood, and a lack of prioritization of the child's needs. Social actors confidently evaluate this practice as illegal, flawed, absurd, and time-consuming. In these evaluations, their discourse focuses on the clear violation of rights and illegality, law discourse, when positioning themselves in relation to the different issues that permeate the practice under investigation. All of this constitutes obstacles to the effective and proper functioning of this practice and means that many children and adolescents grow old in foster care institutions without being able to be placed with a substitute family.